Evaluation of cardioprotective effect of Achyranthes Aspera on isoproterenol induced myocardial infarction in rats - PAPER RETRACTED - SHAIK ELIYAS (International Journal of Pharma and Bio Sciences, 2017)
The present study was designed to investigate the cardio protective effect of hydro alcoholic extract of A. aspera whole plant (AAPE) against isoproterenol induced myocardial infarction in rats. Male wistar albino rats (200-250gm) were pre-treated with AAPE (250 and 500 mg/kg) for 28 days. After the pre-treatment period, myocardial infarction in rats was induced by isoproterenol (ISO) administration (85 mg/kg, S.C.) at an interval of 24 h for two consecutive days. Isoproterenol administration showed significant elevation in the serum levels of cardiac injury markers (creatine kinase-MB, lactate dehydrogenase, alkaline phosphatase, aspartate transaminase and alanine transaminase, Total Proteins), lowered antioxidant defence status (Catalase, SOD, GSH, and LPO) in the heart. AAPE (low and high dose) pre-treatment restored ISO induced altered levels of marker enzymes and disturbed antioxidant status in rats. It was further confirmed by the Histopathological studies. In the AAPE alone treated group no significant alterations were observed. Results of the present study suggest that AAPE has a significant dose dependent protective effect on heart against isoproterenol induced myocardial infarction probably by improving endogenous antioxidant enzyme activities.